Alcohol and Drug Use During Adolescence: Problems and Solutions that Youth Professionals Need to Know - Kate Fogarty; Mark A. Brennan (EDIS, 2005)
Adolescents use and abuse of a variety of substances is an increasingly common concern for Extension agents. Youth professionals must be made aware of this problem and anticipate how the teens and their families they work with may be affected. In addition, the public needs to know that community and youth programs are useful deterrents to drug and alcohol abuse. Community and youth activities can provide opportunities for children and youth to engage in constructive activities and encourage norms that discourage drug/alcohol experimentation. By fostering such environments, Extension agents can actively involve youth in programs, while also directly contributing to their personal development. Statistics on the problem at a national and local level, solutions at the community and family levels, and implications for extension programming will be discussed. This document is FCS9231, one of a series of the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2005.